BRAF mutation screening in melanoma. Issue 4 (August 2015) - Nardin, Charlée; Puzenat, Eve; Prétet, Jean Luc; Algros, Marie Paule; Doussot, Alexandre; Puyraveau, Marc; Mougin, Christiane; Aubin, François
<x xml:space="preserve">Abstract</x> As the detection of the BRAF V600E mutation has a direct impact on treatment decision, an accurate screening for BRAF mutations in patients with advanced or metastatic melanoma is mandatory. Nevertheless, BRAF oncogene mutation status between different samples from the same patient has been studied with conflicting results. This study investigated the intrapatient homogeneity of BRAF mutation status using pyrosequencing in primary tumors and different metastatic sites of melanoma patients. Paired samples of lymphatic, visceral, and subcutaneous metastases and primary melanoma from 45 metastatic melanoma patients were tested for BRAF mutations using a pyrosequencing assay and by Sanger sequencing. Overall, sequencing for BRAF mutation status was performed in 114 paired samples from 45 patients. Eighteen patients (40%) carried a BRAF mutation, including BRAF V600E (12/18), BRAF V600K (5/18), and BRAF V600R (1/18) mutations. Multiple BRAF mutations (V600E and V600K) were found in one patient. Among the patients with BRAF mutations, a good agreement in BRAF mutation status was found between the first and second tumor samples genotyped (91%; Cohen's κ coefficient: 0.81). Discordance in BRAF mutation status was found only in four patients, involving all three patients in whom sentinel lymph node (SLN) metastases were sampled. These SLNs exhibited a wild-type genotype and were discordant with the other BRAF-mutated samples found in the same patient. The intrapatient BRAF status was predominantly homogeneous. However, SLN genotyping using pyrosequencing might be inaccurate in determining the actual mutation status of melanoma. Further studies are required to confirm the lack of reliability of SLN.